Descriptive Spatial Analysis of Human-Elephant Conflict (HEC) Distribution and Mapping HEC Hotspots in Keonjhar Forest Division, India - Tripathy, Bismay Ranjan; Liu, Xuehua; Songer, Melissa; Kumar, Lalit; Kaliraj, Senipandi; Chatterjee, Nilanjana Das; Wickramasinghe, W. M. S.; Mahanta, Kirti Kumar (Frontiers in Ecology and Evolution, 2021)
Escalation of human-elephant conflict (HEC) in India threatens its Asian elephant (Elephas maximus) population and victimizes local communities. India supports 60% of the total Asian elephant population in the world. Understanding HEC spatial patterns will ensure targeted mitigation efforts and efficient resource allocation to high-risk regions. This study deals with the spatial aspects of HEC in Keonjhar forest division, where 345 people were killed and 5145 hectares of croplands were destroyed by elephant attack during 2001 to 2018. We classified the data into three temporal phases (HEC1: 2001-2006, HEC2: 2007-2012 and HEC3: 2013-2018), in order to (1) derive spatial patterns of HEC; (2) identify the hotspots of HEC and its different types along with number of people in the high-risk zones; and (3) assess the temporal change in the spatial risk of HEC. Significantly dense clusters of HEC were identified in Keonjhar and Ghatgaon forest ranges throughout the 18 years, whereas Champua forest range became a prominent hotspot since HEC2. The number of people under HEC risk escalated from 14724 during HEC1 and 34288 in HEC2, to 65444 people during HEC3. Crop damage was the most frequent form of HEC in the study area followed by house damage and loss of human lives. Risk mapping of HEC types and high priority regions that are vulnerable to HEC, provides a contextual background for researchers, policy makers and managers.